Counselling children : a practical introduction - Geldard, Kathryn; Geldard, David; Foo, Rebecca Yin. (Thousand Oaks, CA : SAGE, 2013)
This book is a must have for anyone training to work with children. It combines theory, research-based strategies and direct experience to create a practical, accessible and thoughtful guide. New counsellors will no doubt continue to refer to the book's suggested strategies and media for years to come. This fully revised fourth edition includes a new chapter on Ethical Considerations; a new chapter covering Historical Background and Contemporary Ideas, helping you understand and demonstrate the evidence base for your practice; and lots more case studies to help you develop appropriate techniques across different settings and at different stages of your practice. The book is invaluable in the practical skills training of counsellors, psychologists, social workers, occupational therapists, nurses, teachers, and other professionals who work with children.
1. Counselling children -- 2. Practice frameworks -- 3. Child counselling skills -- 4. Play theory - use of media and activities -- 5. The use of worksheets -- 6. In conclusion.
Previous ed.: 2008.
Includes bibliographical references (p. [327]-335 and index.
Keywords: Children -- Counseling of; Child psychotherapy